Detoxification of soybean oil mill effluent using anaerobic digestion and the suitability of the digestate for fertigation - Ezinne E Okorie; Abubakar Ibrahim (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The upsurge of vegetable oil production in Nigeria and the equally increasing concern for the environment which arises due to indiscriminate disposal of phytotoxic vegetable oil mill effluent in a less regulated country like Nigeria makes the re-use of the effluent for fertigation a suitable strategy for its disposal if the appropriate treatment technique is adopted. Method  A laboratory experiment was set up to study how the detoxification of soybean oil mill effluent (SOME) under different anaerobic digestion time (0, 20 and 40 days) and application rates (0, 50 and 100 m3/ha) will influence the suitability of the effluent for fertigation. Results SOME has a pH of 8.3, which decreased steadily to 7.4 as digestion time increased to 40 days. EC and potassium levels also decreased as digestion time increased, from 0.37 dS/m and 120.6 g/l to 0.28 dS/m and 70.1 g/l, respectively. However, levels of organic carbon, nitrogen and phosphorus did not change significantly. The effluent impacted negatively on germination after a one-time application, with the germination index going as low as 22% for untreated SOME and gradually increasing to 66% as digestion time increased. Continuous application of the untreated effluent also affected soil microbial activity negatively when compared to the treated effluent. Conclusion Anaerobic digestion detoxifies SOME and the efficiency of the treatment increased with increasing digestion time. The effluent also contains low to moderate amounts of NPK and therefore has a potential for fertigation.